Specimen size effect on the splitting-tensile behavior of coral aggregate concrete: A 3D mesoscopic study. (September 2021) - Wu, Zhangyu; Zhang, Jinhua; Yu, Hongfa; Fang, Qin; Ma, Haiyan
Highlights: Three-dimensional random mesoscale modelling for coral aggregate concrete (CAC). Splitting-tensile failure patterns and failure processes of CAC. Splitting-tensile failure mechanism of CAC. Strain rate effect and size effect on the splitting-tensile behavior of CAC. Strain effect law and size effect law of CAC under splitting-tensile loading. Abstract: The paper presents a mesoscopic investigation into the effects of specimen size and strain rate upon the strength and failure modes of coral aggregate concrete (CAC) subjected to splitting-tensile load. A three-dimensional (3D) mesoscale model that assumes concrete as a three-phase composite, i.e., aggregate, mortar and interfacial transitional zone (ITZ), was established for simulating the splitting-tensile behaviors of CAC at different strain rates (10 −5 ∼ 200 s −1 ). The mesoscopic deformation and failure patterns of CAC cylinders with different sizes were exhibited through the 3D mesoscale modelling. Emphasis was set on the specimen size- and strain-rate effect on the tensile strength of CAC and corresponding effect laws were finally expressed by the mathematical statistical method. The numerical results suggest that there is a rate-hardening effect on the tensile strength of CAC, and the strain-rate effect is more noticeable when the critical strain-rate (1 s −1 ) is reached. Taking into the varying strengths at low- and high strain rate, the piecewise formulas were determined by the numerical and available test results to represent the strain-rate effect on CAC. In accordance with the relationship between the splitting-tensile strength and fracture area of specimen, the size-effect law of CAC at various strain rates was mathematically expressed using a series of power functions, which is of great significance for future research and application of CAC.